Legal Efforts For The Parties To The Sale and Purchase Agreement of Goods (Comparative Study of The United Nation Convention on Contracts For The International Sale of Goods (CISG) Provisions and The Civil Code in International Trade) - Shelly Yusika (Institute Of computer Science (IOCS), 2020)
A sale-purchase agreement is a type of reciprocal agreement that involves two parties, namely the seller and the buyer. Both parties who make a sale-purchase agreement each have the right and obligation to carry out the contents of the agreement they made. As in general, an agreement is a legal institution based on the principle of freedom of contract where the parties are free to determine the form and content of the type of agreement they make. However, the freedom to make an agreement will be different if it is carried out in a wider scope involving parties from countries with different legal systems. Each country has its own provisions which may differ from one another. This research is entitled: Legal Efforts for the Parties in the Sale-Purchase Agreement of Goods (Comparative Study of the Provisions of The United Nation Convention on Contract for the International Sale of Goods (CISG) and the Civil Code in International Trade). The problems that will be discussed from this research are: How to regulate the rights and obligations of the parties in a sale and purchase agreement in international trade both in the Civil Code and The United Convention On Contract For The International Sale Of Goods (CISG) as well as legal remedies that can be taken by the parties. parties in the event of an international trade dispute in the Civil Code and The United Convention On Contract For The International Sale Of Goods (CISG) This research is normative legal research. The first step is to carry out normative legal research based on secondary legal materials, namely an inventory of regulations relating to contracts and buying and selling of goods internationally, both contained in the Civil Code and in The United Convention On Contract For The International Sale Of Goods (CISG). ). In the CISG legal remedies for sellers and buyers in the event of a dispute on the implementation of the agreement are divided into three categories, namely in terms of breach of contract, fundamental contract, and anticipatory breach. In the Civil Code, legal remedies for the parties in the sale-purchase agreement are regulated in Article 1236-1243 of the Civil Code in the event of a specific default and default, each of which has different consequences and duration of filing a lawsuit. Meanwhile, the claim for compensation is regulated in Articles 1243-1252 of the Civil Code.